Pendampingan Rebranding Logo Dan Kemasan Guna Meningkatkan Penjualan UMKM Opak Gapit - Moch. Rafie Pratama; Endang Iryanti (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Micro, Small and Medium Enterprises or known as MSMEs are an important sector of the domestic and global economy. The research was conducted in Talang Village, Rejoso District, the subject of this research was Bu Yanti's Opak Gapit MSMEs. Opak Gapit is one of the leading MSMEs in Talang Village. The problem faced by opak gapit is the lack of use of the brand and there are weaknesses in the packaging of opak gapit if it has to be sent out of town. So that it is necessary to rebrand the Opak Gapit MSMEs, the changes made include making a logo, updating the packaging design and taking product photos. The results of that research succeeded in developing packaging in terms of design and functional value. The new design looks more attractive to consumers and up to date when compared to the old design.